An Investigation into Thinning Cycles for Young Chir (Pinus longifolia) at New Forest, Dehra Dun - Krishnaswamy, V. S.; Mathauda, G. S. (Indian Forester, 1953)
The description and results of a thinning cycle investigation that has been in progress since 1936 in young chir crops at Dehra Dun are given. The thinning cycles under trial are 4, 8 and 12 years, the intensity in all cases being, ’D’ grade of ordinary thinnings. The shortest thinning cycle has given maximum diameter increment and largest number of trees in the top diameter classes. Its performance is comparable to that of the 8 years cycle from the view-point of basal area and volume production, while the 12 years cycle has given distinctly poorer results. The treatments have had no influence on height growth and the length of clean bole. The 4 year thinning cycle, therefore, gives maximum diameter increment as well as total volum, without impairing the quality of the timber. The thinning periodicity may be increased to 8 years without adversely affecting total volume production. The investigation also indicates that thinning intensities lighter than the ordinary ’D’ grade should be avoided for high quality young chir crops.